2021
DOI: 10.1155/2021/2183427
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Korean Mistletoe Extract as an Anti-Inflammatory Supplementation

Abstract: Korean mistletoe has anti-inflammatory and antioxidant functions and may be a useful training supplement. We investigated the effect of Korean mistletoe extract (KME) on inflammatory markers after high-intensity exercise by 20 university male rowers (KME group vs. CON group) consuming 110 mL KME/dose (2 times a day over 8 weeks). Blood samples were collected for measurement of serum cytokine levels at baseline, immediately after exercise, and following 30 minutes of recovery. Interleukin-6 (IL-6), tumor necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
1
5
1
Order By: Relevance
“…A lack of alterations in performance with VA is in direct opposition to previous reports although no changes in HR are supported [13,14]. In contrast to current findings, Ha et al used an identical exercise bout but showed improved rowing efficiency (i.e., individuals took fewer strokes to complete the rowing trial in a similar time) following 8 weeks of twice-daily VA supplementation [14].…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…A lack of alterations in performance with VA is in direct opposition to previous reports although no changes in HR are supported [13,14]. In contrast to current findings, Ha et al used an identical exercise bout but showed improved rowing efficiency (i.e., individuals took fewer strokes to complete the rowing trial in a similar time) following 8 weeks of twice-daily VA supplementation [14].…”
Section: Discussioncontrasting
confidence: 89%
“…Although VA has been used for centuries in folk medicine, the nutraceutical benefits have only recently been empirically investigated. Initial studies in animals and humans support the use of chronic VA supplementation as a means to improve aerobic exercise performance and possibly enhance oxidative capacity [2,4,14]. However, little to no information exists as to whether an acute dose of VA, which may be more practical for some individuals, imparts a performance enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations